THE IMPACT OF ALGAL DIVERSITY ON MAKHANA GROWTH IN THE SELECTED PONDS OF THE DARBHANGA DISTRICT - Hari om yadav; Dr. Dilip Kumar Jha (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
In recent years, problems have arisen in makhana fish aquaculture, makhana agriculture, and all other makhana-based farming systems due to a small aquatic weed, specifically algae. Algae are becoming a significant problem in makhana-based cropping systems, leading to a decline in yield and a decline in water quality. Cyanophycean, Euglenophyceae, Chlorophyceae, and Bacillariophyceae algae species from Makhana Pond in the Darbhanga district served as the study’s representatives. Non-hetrocystous cyanobacteria were more prevalent in all sampling sites, especially in soil with a high organic and nitrogen content, but cyanobacteria were prevalent in the research site. This addition broadens the systematic knowledge of the algae in Makhana Pond. Throughout the investigation, it showed a trimodal pattern of changes. Two minor highs occurred in November and April, while one occurred in June. In the months of June through August, its population decreased. Throughout the study period, the overall population of blue green algae outnumbered both diatoms and green algae. Diatoms made up a larger percentage of the composition from July to November, although they were less prevalent than blue greens. Summertime had the highest Gross Primary Productivity (GPP), which calculates the overall rate of photosynthesis including the organic matter used up in respiration, while wintertime saw the lowest.